Reproducing Power through Classroom Discourse: A Critical Discourse Analysis of Teacher–Child Interaction in Non-Formal Preschool Education - Sri Meiti Anggraini Ahaya; Nonny Basalama (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study investigates teacher–child interaction in non-formal preschool education for children aged 0–4 years using Critical Discourse Analysis (CDA). It addresses a research gap in classroom discourse research, which has predominantly focused on formal education, while non-formal early childhood settings remain underexplored. The study aims to examine how teachers’ language organizes interaction, regulates children’s participation, and reproduces classroom power relations. A qualitative design was employed in a non-formal playgroup in Kecamatan Suwawa, Indonesia. Data were collected from eight classroom observation sessions conducted over four weeks, involving one teacher and fifteen children aged 0–4 years. Each session lasted approximately 60–90 minutes. Classroom interactions were audio-recorded, transcribed, and analyzed using Fairclough’s three-dimensional CDA framework. The findings show that teacher talk is dominated by imperative speech acts (75%), followed by interrogatives (20%) and declaratives (5%). Display questions (70%) are used more frequently than referential questions (30%), indicating that interaction remains largely teacher-directed. From a critical perspective, these patterns normalize teacher authority and limit children’s dialogic participation. The study highlights the persistence of hierarchical interactional structures in non-formal preschool settings and provides insights for promoting more participatory classroom communication.